2018
DOI: 10.1188/18.cjon.37-52
|View full text |Cite
|
Sign up to set email alerts
|

Sleep-Wake Disturbance: A Systematic Review of Evidence-Based Interventions for Management in Patients With Cancer

Abstract: Cognitive behavioral intervention/approach is the only intervention that is recommended for practice. Mindfulness-based stress reduction and exercise interventions are likely to be effective but require more evidence. Pharmacologic interventions, relaxation, imagery, meditation, acupuncture, yoga, massage, and psychoeducation have insufficient evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 112 publications
1
25
0
Order By: Relevance
“…The results of this study showed that the Internet-based self-management intervention was more effective than general care program in improving sleep quality among cancer patients with fatigue, which was consistent with Matthews et al 36 Trudel-Fitzgerald et al 37 survey showed that the most common symptom of breast cancer patients was insomnia, which was closely related to CRF. About 73.5% of breast cancer patients were experiencing insomnia problems with different severity and frequency, and some patients even were troubled by sleep-related distress.…”
Section: Discussionsupporting
confidence: 88%
“…The results of this study showed that the Internet-based self-management intervention was more effective than general care program in improving sleep quality among cancer patients with fatigue, which was consistent with Matthews et al 36 Trudel-Fitzgerald et al 37 survey showed that the most common symptom of breast cancer patients was insomnia, which was closely related to CRF. About 73.5% of breast cancer patients were experiencing insomnia problems with different severity and frequency, and some patients even were troubled by sleep-related distress.…”
Section: Discussionsupporting
confidence: 88%
“…Interventions to improve poor sleep in BC patients have been developed and tested for use when sleep is the primary or only symptom [25]. Meta-analysis results provide a strong quality of evidence and large effect sizes for the use of cognitive behavior therapy (CBT) in cancer survivors [44].…”
Section: Discussionmentioning
confidence: 99%
“…The National Comprehensive Cancer Network (NCCN) Guidelines for Cancer-Related Fatigue [45] and Survivorship [46] recommend a personalized physical activity/exercise program for patients during and after treatment. Likewise, the Oncology Nursing Society Putting Evidence into Practice (ONS-PEP) resource rates CBT as "Recommended for Practice" and physical activity/exercise as "Likely to be Effective" to reduce poor sleep [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two interventions which may have promise for treating sleep disturbance are exercise 20 and cognitive behavioral therapy 51 .…”
Section: The Mismatch Between Subjective and Objective Measures Of Sleepmentioning
confidence: 99%